Hist?ria, cinema e representa??es sobre ind?genas: uma an?lise de Caramuru, a inven??o do Brasil - Souza, Mabel Freitas Araujo de (2016)
This paper discusses the relationship between fictional cinema and Brazilian historiography in the construction and perpetuation of representative images on indigenous peoples. We seek to map the first representations regarding these people and how they are still present in the collective imagination . The filmCaramuru, a inven??o do Brasil, the main source and object of this work was taken as an example of filmic production of the period (1995-2005), the analyzed emphasizing the celebrations of 500 years of Brazil. It sought to explore the historical context in which the film was produced and launched, aiming to understand the forms of representation and also highlight the similarities of the filmic discourse in relation to the discourses contained in some works of Brazilian historiography.